A scientometric study of unsafe behavior through Web of Science during 1991–2020. Issue 4 (2nd October 2022) - Malakoutikhah, Mahdi; Alimohammadlou, Moslem; Rabiei, Hadiseh; Faghihi, Seyed Aliakbar; Kamalinia, Mojtaba; Jahangiri, Mehdi
ABSTRACT: Objectives . This scientometric study aimed to investigate research and hot topics on unsafe behavior. Methods . The study was performed using scientometric analysis mapping tools, such as CiteSpace, Gephi, MINITAB and VOSviewer, for statistical analysis. Studies published in Web of Science were included. Results . The first study was published in 1987. The results of the study showed that the Safety Science journal with 111 studies (10.45%) presented most of the published studies in this field. The USA and China were the two highest producing countries, with 289 and 229 published studies, respectively. The results of keywords and hot topics showed that between 1991 and 2000 safety climate, safety performance and modeling were ranked as the first to third most frequent words, and during 2001–2010 safety performance was removed from the list of top 10 keywords while safety climate and modeling were ranked, respectively, ninth and sixth most frequent. Finally, between 2011 and 2020, the keyword of organizational factors rose to first rank, indicating the significance of this keyword in the future. Conclusions . According to the results of the present study, it can be concluded that future studies on unsafe behavior can be conducted in the field of organizational factors.